Analysis of Service Effectiveness and Operation Policy of Trans Metro Bandung (TMB) using Customer Satisfaction Index (CSI) and Fishbein Method - Galuh Ramadhan Mangku Praja; Fauzia Mulyawati; Hedy Rahadian; Ignatius Sudarnoso (Almana : Jurnal Manajemen dan Bisnis, 2022)
Bandung is a developing city. Focus on Areas of Service Effectiveness Analysis and Operational Policies of Trans Metro Bandung (TMB) Bandung City Using the Customer Satisfaction Index (CSI) and Fishbein Methods. Trans Metro Bandung (TMB) is one of the transportation options in the city of Bandung. However, along with advances in transportation technology, many choices of this cause congestion in the city of Bandung because it is dominated by private vehicles, the lack of application of orientation to the use of public transportation in Bandung. This study aims to determine the optimization of Trans Metro Bandung using a qualitative approach with a descriptive method. Later this can be an evaluation material for UPT Trans Metro Bandung by looking at the results of the analysis of the customer satisfaction index (CSI) with a value of 63.12 and Fishbein with a value of 283.41, perceived by consumers as less effective with the description "Ineffective".